2020
DOI: 10.1038/s41598-020-77846-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic analysis by SWATH-MS unravels the most dominant mechanisms underlying yeast adaptation to non-optimal temperatures under anaerobic conditions

Abstract: Elucidation of temperature tolerance mechanisms in yeast is essential for enhancing cellular robustness of strains, providing more economically and sustainable processes. We investigated the differential responses of three distinct Saccharomyces cerevisiae strains, an industrial wine strain, ADY5, a laboratory strain, CEN.PK113-7D and an industrial bioethanol strain, Ethanol Red, grown at sub- and supra-optimal temperatures under chemostat conditions. We employed anaerobic conditions, mimicking the industrial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Ethanol Red response to this supraoptimal temperature was found to trigger mechanisms like repression of proteins involved in arginine biosynthesis (Arg1, Arg5, Arg6, and Arg8) and induction of a protein (Car2). The latter catalyzes arginine degradation, guaranteeing glutamate conservation and proline production, which is thought to be involved in stress protection . This, though, does not occur in CEN.PK113-7D .…”
Section: Resultsmentioning
confidence: 68%
“…Ethanol Red response to this supraoptimal temperature was found to trigger mechanisms like repression of proteins involved in arginine biosynthesis (Arg1, Arg5, Arg6, and Arg8) and induction of a protein (Car2). The latter catalyzes arginine degradation, guaranteeing glutamate conservation and proline production, which is thought to be involved in stress protection . This, though, does not occur in CEN.PK113-7D .…”
Section: Resultsmentioning
confidence: 68%
“…Additionally, the thermotolerant industrial strains presented significantly higher trehalose accumulation compared to the reference laboratorial CEN.PK113-7D strain. At the proteome level, temperature responses also differ between S. cerevisiae strains [30]. Interestingly, thermotolerant S. cerevisiae Ethanol Red response to both supra and sub-optimal temperature involved the overexpression of Erg13-a protein involved in early ergosterol biosynthesis-and Gsy1-a glycogen synthetase [30].…”
Section: Robustness Of the Fermentation Organismmentioning
confidence: 99%
“…Recently, the differential proteomic responses of three distinct S. cerevisiae strains, an industrial wine strain, ADY5, a laboratory strain, CEN.PK113-7D and an industrial bioethanol strain, Ethanol Red, grown at sub- and supra-optimal temperatures were studied under chemostat conditions, mimicking the industrial processes [ 29 , 32 ]. The proteomic profile of these strains was performed by SWATH-MS, allowing the quantification of 997 proteins [ 32 ]. Overall, proteomic data evidenced that at high temperature (39°C), the amino acid biosynthetic pathways and metabolism represent the main function recruited [ 32 ].…”
Section: Improvement Of Process-related Traitsmentioning
confidence: 99%
“…The proteomic profile of these strains was performed by SWATH-MS, allowing the quantification of 997 proteins [ 32 ]. Overall, proteomic data evidenced that at high temperature (39°C), the amino acid biosynthetic pathways and metabolism represent the main function recruited [ 32 ]. The variability of responses of the three strains examined showed that no general rules can be assumed for different S. cerevisiae strains, and that the temperature-response is highly dependent on their genetic and environmental background [ 32 ].…”
Section: Improvement Of Process-related Traitsmentioning
confidence: 99%
See 1 more Smart Citation